PENGARUH PROFITABILITAS DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN NON-KEUANGAN DI INDONESIA - Wijaya, Vanessa Natalia; Tjhai, Fung Jin (E-Jurnal Akuntansi TSM, 2023)
Firm value is one of the factors that can affect the decision taken by investors. The aim of this research is to obtain empirical evidence related to the influence of several independent variables on one dependent variable. The dependent variable used in this research is firm value that measured by Tobin’s Q. This research is also has independent variables consisting of profitability, capital structure, managerial ownership, dividend policy, firm size, liquidity, and institutional ownership. The results of this research show that profitability has an unstandardized coefficient value of 7.383, so it can be concluded that profitability has a positive effect on firm value. This also shows that the higher profitability of the company, it proves that a company is running well, so this also influences investors views on whether to invest in a company or not. On the other hand, capital structure, managerial ownership, dividend policy, company size, liquidity, and institutional ownership has no effect on firm value.